Representation of land and ownership in the Zimbabwean public media - Mushore, Washington (Unknown, 2016)
Using framing theory, the aim of this paper is to critically explore or unpack the language frames through which the concept of land and ownership was discussed in the Zimbabwean Public Media during the Land Reform exercise, also known as Third Chimurenga or "Fast track Land Reform Exercise" and which was ernestly conducted in the period 2000 - 2008. The paper argues that the Public Media as represented in this article by The Herald newspaper viewed land as belonging to the black majority or the Native people of Zimbabwe. Ownership of land, according to the Public Media was legitimised generally through skin colour and place of birth. Accordingly, land belonged to the Native/black people of Zimbabwe. In this respect, the Public Media took a positive stance toward the inevitability of the Land Reform programme. However, the Public Media did not clearly state whether all black people had equal access to the land or had the same right to own land. This position will, thus, be exemplified through The Herald newspaper stories which were purposively sampled in the period mentioned above.